Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1016/j.jacc.2010.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Iodofiltic Acid I 123 (BMIPP) Fatty Acid Imaging Improves Initial Diagnosis in Emergency Department Patients With Suspected Acute Coronary Syndromes

Abstract: The addition of BMIPP data to the initially available clinical information adds incremental value toward the early diagnosis of an ACS, potentially allowing determination of the presence or absence of ACS to be made earlier in the evaluation process. (Safety and Efficacy Iodofiltic Acid I 123 in the Treatment of Acute Coronary Syndrome [Zeus-ACS]; NCT00514501).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…In an open-label phase IIA clinical trial, the utility of fatty acid metabolism with 123 I-BMIPP to detect myocardial ischemic memory was shown up to 30 h after exercise-induced ischemia (10). In a subsequent phase III clinical trial, the safety and efficacy of 123 I-BMIPP were evaluated in patients presenting to an emergency department with symptoms suggestive of acute coronary syndrome (12). When the 123 I-BMIPP data were added to the initial clinical diagnosis alone, the sensitivity for the acute coronary syndrome diagnosis nearly doubled without sacrificing specificity.…”
Section: Novel Findings and Applications: A Tale Of 3 Radiotracersmentioning
confidence: 99%
“…In an open-label phase IIA clinical trial, the utility of fatty acid metabolism with 123 I-BMIPP to detect myocardial ischemic memory was shown up to 30 h after exercise-induced ischemia (10). In a subsequent phase III clinical trial, the safety and efficacy of 123 I-BMIPP were evaluated in patients presenting to an emergency department with symptoms suggestive of acute coronary syndrome (12). When the 123 I-BMIPP data were added to the initial clinical diagnosis alone, the sensitivity for the acute coronary syndrome diagnosis nearly doubled without sacrificing specificity.…”
Section: Novel Findings and Applications: A Tale Of 3 Radiotracersmentioning
confidence: 99%
“…In patients with acute chest pain presenting to the emergency department, a cardiac BMIPP scan within 30 hours of the last episode of chest pain provides incremental value to clinical data in establishing the early diagnosis of acute coronary syndromes. 20 An abnormal BMIPP study also has been shown to have good diagnostic accuracy and prognostic utility in …”
Section: Cardiac Fatty Acid Metabolism Radionuclide Imaging For Myocamentioning
confidence: 99%
“…Kontos et al [25] conducted a multicenter trial to evaluate the efficacy and safety of BMIPP in patients presenting to the emergency department with symptoms suggestive of ACS. A total of 507 patients with no history of prior infarction were enrolled at 50 centers in the United States and Canada.…”
Section: Recent Developments In Fa Imaging Of Myocardial Ischemiamentioning
confidence: 99%
“…Patients underwent resting BMIPP imaging within 30 h of cessation of symptoms. The efficacy population consisted of the 448 patients who received an adjudicated final diagnosis of ACS (defined as a positive troponin; ST-segment depression on electrocardiography; an angiographically visible culprit lesion; inducible ischemia on myocardial perfusion imaging; and/or coronary revascularization, infarction, or death during a 30-day follow-up period), intermediate likelihood ACS (defined as borderline cardiac troponin levels; a 70% to 89% coronary stenosis in the absence of a culprit lesion; or coronary revascularization in the absence of a positive perfusion imaging study), or negative ACS [25]. The sensitivity of BMIPP imaging alone for the diagnosis of ACS was 73%, compared with a sensitivity of only 43% for a clinical diagnosis.…”
Section: Recent Developments In Fa Imaging Of Myocardial Ischemiamentioning
confidence: 99%